Recepcja koncepcji pedagogicznych Édouarda Séguina w pedagogice Drugiej Rzeczypospolitej - Fetzki, Tomasz (Biuletyn Historii Wychowania, 2017)
The article discusses the direct and indirect influence that the concepts of Édouard Séguin, creator of a pedagogy for people with intellectual disabilities, had on the development of Polish special and general pedagogy in the interwar period. It also presents a brief overview of the biography and achievements of this Franco-American pedagogue and doctor.